1999
DOI: 10.1046/j.1471-4159.1999.0721040.x
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effects of Glycolipid Biosynthesis Inhibitors on Ceramide‐Induced Cell Death in Neuroblastoma Cells

Abstract: An in vitro model of Gaucher's disease in murine neuroblastoma ϫ rat glioma NG108-15 cells was used to investigate the physiological effects of two specific inhibitors of glucosylceramide synthase, d,l-threo-1-phenyl-2-decanoylamino-3-morpholino-1-propanol (d,l-PDMP) and N-butyldeoxynojirimycin (NB-DNJ), which have been suggested as agents for treatment of glycolipid storage disorders. Incubation of NG108-15 cells with conduritol-B-epoxide, a covalent inhibitor of glucosylceramidase, raised the intracellular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(23 citation statements)
references
References 56 publications
0
23
0
Order By: Relevance
“…However, as our results show, both PDMP enantiomers strongly and equally reduced the ceramide content, specifically the long-chain ceramide species (≤18C), while NB-DNJ did not. At first sight, this could be surprising because D-PDMP is usually described as a ceramide-accumulating agent (Bieberich et al, 1999, Huang et al, 2011, Radin et al, 1993, Takasugi et al, 2015, Yu et al, 2012. Indeed, when blocking the conversion of ceramides to GlcCer, it could be expected that an accumulation of ceramides may have occurred.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, as our results show, both PDMP enantiomers strongly and equally reduced the ceramide content, specifically the long-chain ceramide species (≤18C), while NB-DNJ did not. At first sight, this could be surprising because D-PDMP is usually described as a ceramide-accumulating agent (Bieberich et al, 1999, Huang et al, 2011, Radin et al, 1993, Takasugi et al, 2015, Yu et al, 2012. Indeed, when blocking the conversion of ceramides to GlcCer, it could be expected that an accumulation of ceramides may have occurred.…”
Section: Discussionmentioning
confidence: 99%
“…*p b 0.05, **p b 0.01, ***p b 0.001 compared to the control cells. (Bieberich et al, 1999;Guerrera and Ladisch, 2003;Platt et al, 1994). Treatment with 50 μM NB-DNJ for 3 and 5 days induced a significant drop in the rate of gangliosides, comparable to that observed with D-PDMP (Fig.…”
Section: Effects Of D-and L-pdmp On Metabolic Precursors Of Gangliosidesmentioning
confidence: 99%
“…In addition, analogous prior studies showed that blockade of GlcCer synthase by 1-phenyl-2-decanoylamino-3-morpholino-1-propanol (PDMP) or 1-phenyl-2-palmitoylamino-3-morpholino-1-propanol (PPMP), specific inhibitors of GlcCer synthase, can lead to Cer accumulation in cells (47), whereas other GlcCer synthase inhibitors, e.g. N-butyldeoxynojirimycin, decrease GlcCer production without accumulation of Cer (48). These differences are thought to reflect 1-phenyl-2-decanoylamino-3-morpholino-1-propanol or 1-phenyl-2-palmitoylamino-3-morpholino-1-propanol, but not N-butyldeoxynojirimycin, inhibition of the conversion of Cer to 1-O-acylCer, resulting in Cer accumulation (49).…”
mentioning
confidence: 88%
“…Sphingolipids have been implicated in inflammatory and apoptotic processes [5] and glucosylceramide might have direct activating or enhancing effects on macrophage function [6], possibly mediated through selective calcium channel dysregulation. Indeed, several indicators of macrophage activation, including chitotriosidase, CCL18 , angiotensin-converting enzyme [7] and cathepsin S, have been identified in excess in the plasma of patients with GD.…”
Section: Outline Of the History Of Gaucher Diseasementioning
confidence: 99%